Ways of Mycogenetic Decomposition of Wood in the Forest Ecosystems of Specially Protected Natural Territories of the Republic of Abkhazia - S.I. Khacheva (Учёные записки Казанского университета: Серия Естественные науки)
This paper discusses ways of mycogenetic decomposition of wood (saprotrophic, phytopathogenic, corrosive, and destructive) in different forest ecosystems within the specially protected natural territories of the Republic of Abkhazia with regard to the ecological and biological features of xylotrophic fungi. Data on the distribution of aphyllophoroid fungi along the forest types, as well as their spread depending on habitat conditions in the altitude range from 5 to 1980 m above sea level, are discussed. It has been the first time when the methodical study of the species composition of aphyllophoroid fungi was performed. Regularities of their substrate confinement have been determined. The dominant complex of fungi species destructing the main wood substrates in different forest associations has been revealed.